Penerapan Asas Keadilan dalam Perkara Perdata pada Lembaga Lelang Penjualan Barang: Relevansi, Peluang dan Tantangannya - Cindy Rachmadewi Ariyanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Execution auctions have the characteristics of the seller of the goods being an agency or institution. This character has implications for legal substances that serve as guidelines in the auction process, which must conform to statutory regulations. The purpose of this research is to know and analyze the relevance of the principles of justice, the opportunities for the principles of justice and the challenges of the principles of justice in the execution of civil cases at auctions for the sale of goods. The research method uses a normative juridical approach. Legal norms which are the legal substance of execution in the law of goods auctions are analyzed through a concept and law approach. This research finds that first, the principle of law (fairness) is very relevant to the law of execution auctions. This relationship is caused by the need for auction legal norms which require the legal principle of justice as a guide if there is a conflict of legal norms in its implementation or application. Second, the opportunity for the legal principle of justice, in the philosophical realm to become a legal principle in the treatises on auctions, namely for the sake of justice in the belief in the One Almighty God. The sociological domain is a guide and guideline for the eroding of the jungle law of disputes over auction results. The juridical realm becomes a guideline if there is a conflict of norms in every statutory regulation related to auction law. Third, challenges to the legal principle of justice originate from the debtor's rights, legal substance (contents of credit agreements) and legal structures (auction agencies and their implementation).